The muonic atom of Bohr - Bravo, Jorge A. (2017)
The theory that Bohr applied in 1913 to describe the electronic orbitals is extended to the muonic orbitals in a muonic atom. There is a possibility that for nuclides with suﬃciently large atomic number, these orbitals occupy the nuclear volume and, therefore, the puntual nuclear model that Bohr utilized is not applicable. In this study, we deduce that for nuclides with Z ≥ 46 the Bohr radius of the ﬁrst level stay inner of nuclear volume; also, we deduce that the muonic orbitals with bigger order stay out of nuclear volume.